Influence of insect infestation on aflatoxin contamination of stored maize in four agroecological regions in Benin - Hell, K.; Cardwell, K.; Sétamou, M.; Schulthess, F. (2000)
Insect species and damage levels were evaluated and related to aflatoxin content in maize sampled from farmers' stores in four agroecological zones over a two-year period in Benin, West-Africa. In 1993, no aflatoxin was detected in maize that was free of isect damage. In the same year; in maize with more than 70 % of cobs damaged by insects 30.3 % were aflatoxinpositive, with a mean aflatoxin contamination of 77.8 ppb (parts per billion or kg). Grain moisture increased with damage levels. The mean aflatoxin content of maize infested with Carpophilus dimidiatus Fabricius (Coleoptera: Nitidulidae) was significantly higher than maize free of this pest (F = 5.05, P ~ 0.05). In 1994/95, the density of Mussidia nigrivinella Ragonot (Lepidoptera: Pyralidae), was significantly higher in the Northern Guinea Savanna than in the other zones, and the presence of this pest was positively correlated with the cob area visibly infected with Aspergillus jlavus Link (Deutoremycetes: Monoliales) (r = 0.239, P ~ 0.05) early in storage. Six months later, damage levels due to insects were significantly lower in the Sudan Savanna than in the other ecozones. The infestation level of the most common storage pest, Sitophilus zeamais Motschuisky (Coleoptera: Curcilionidae) decreased from the south to the north. After six months of storage aflatoxin level was positively correlated with the cob area damaged by Sesamia calamistis Hampson (Lepidoptera: Noctuidae) (r = 0.25, P ~ 0.05), the number of Cryptophlebia leucotreta (Meyrick) (Lepidoptera: Tortricidae) observed on maize (r =.26, P ~ 0.05) and cob area damaged by S. zeamais (r = 0.22, P ~ 0.05).